Факторы индукции соматического эмбриогенеза Pinus sibirica Du Tour - Лукина, А.В.; Третьякова, И.Н. (Фактори експериментальної еволюції організмів, 2014)
Aims. In vitro clonal propagation has the potential for fast multiplication of superior genotypes, allowing the exploitation of maximum genetic gain achieved in the breeding program. To determine the proportion of immature zygotic embryos from each open pollinated (OP) and controlled pollinated (CP) family from which somatic embryogenesis could be initiated and the number of responding families using various initiation media. Methods. For initiation of embryogenic cultures five media differs of plant grow regulator and carbohydrates source and concentration were tested. 22 OP and 6 CP trees have been used as zygotic embryo donors. Results. All tested media were capable to support proliferation cells lines P. sibirica. Callus tissue was initiated on explants from all of the 22 trees tested. Great variation in the mean percentage of embryogenic line establishment was observed, depending on the family.